2019
DOI: 10.1016/j.rse.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Directional variation in surface emissivity inferred from the MYD21 product and its influence on estimated surface upwelling longwave radiation

Abstract: The land surface emissivity (LSE) in the MYD21 product contains the effects of viewing zenith angle. The influence of the angular variation of LSE on the surface upwelling longwave radiation (SULR) estimation is still unexplored at the satellite scale. We performed statistical analyses of MYD21 emissivity retrievals over different land surface types for three longwave bands centred around 8.55 µm (Band 29), 11 µm (Band 31) and 12 µm (Band 32), respectively. A look-up table was generated to describe the angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The average ET biases for STIC and SEBS are close to 5 and 15 W m −2 , respectively across different bins of VZA, which is higher for TSEB (∼50 W m −2 ). We infer this is partly because the angular variation of thermal radiation is not pronounced when VZA is below 30° (Ermida et al, 2018;Hu et al, 2019;Mwangi et al, 2022). Moreover, the high spatial homogeneity at the EC sites (Fisher et al, 2020) is also an important factor for the weak angular variation of thermal radiation.…”
Section: Factors Affecting Model Performancesmentioning
confidence: 87%
“…The average ET biases for STIC and SEBS are close to 5 and 15 W m −2 , respectively across different bins of VZA, which is higher for TSEB (∼50 W m −2 ). We infer this is partly because the angular variation of thermal radiation is not pronounced when VZA is below 30° (Ermida et al, 2018;Hu et al, 2019;Mwangi et al, 2022). Moreover, the high spatial homogeneity at the EC sites (Fisher et al, 2020) is also an important factor for the weak angular variation of thermal radiation.…”
Section: Factors Affecting Model Performancesmentioning
confidence: 87%
“…where ε is emissivity and σ is the Stefan-Boltzmann constant. The emissivity was set to 0.985 when the surface was covered by snow (Warren, 1982) and to 0.975 for grassland (Hu et al, 2019) during the snow-free period. No further attempt to constrain the emissivity was conducted for the present data set and doing so is considered ongoing work by the SPLASH team and collaborators.…”
Section: Radiationmentioning
confidence: 99%
“…As a result, this study has prescribed 36 component temperature profiles. Component emissivities . Previous studies indicate that the vegetation emissivity can be treated as a constant with the variation of view angles (Göttsche et al, ) whereas the soil emissivity presents an angular dependency (Hu et al, ; Ren et al, ). García‐Santos et al () revealed that soil emissivity decreases with the increase of θ v , and their relationship can be approximated as follows: εs)(θv=εs)(08.7×109×θvα where α is the parameter to express the strength of angular dependency.…”
Section: Datamentioning
confidence: 99%
“…In fact, like the bidirectional reflectance in visible and near‐infrared (VNIR) region, thermal infrared (TIR) radiation has been proven to own a significant directional signature (Lagouarde et al, ; Lagouarde et al, ; Lagouarde et al, ; Zhang et al, ). This thermal radiation directionality (TRD) effect is mainly resulted from two reasons: (1) the land surface emissivity is angularly dependent (Cao et al, ; Cuenca & Sobrino, ; García‐Santos et al, ; García‐Santos et al, ; Hu et al, ; Sobrino et al, ) and (2) various components of heterogeneous surface have different temperatures (Bian et al, ; Bian et al, ; Li et al, ; Timmermans et al, ). As a result, there are different observation values of thermal radiation or LST under different viewing and illumination geometries (Ermida et al, ; Ermida et al, ).…”
Section: Introductionmentioning
confidence: 99%